Evaluation of improved bi-manual endoscopic resection using a customizable 3D-printed manipulator system designed for use with standard endoscopes: a feasibility study using a porcine ex-vivo model - Walter, Benjamin; Krieger, Yannick S.; Wilhelm, Dirk; Feussner, Hubertus; Lueth, Tim C.; Meining, Alexander (Endoscopy International Open, 2021)
Background and study aims A major drawback of endoscopic en-bloc resection technique is its inability to perform bimanual tasks. Although endoscopic platforms that enable bimanual tasks are commercially available, they are neither approved for various locations nor adaptable to specific patients and indications. Methods Based on evolution of an adaptive 3D-printable platform concept, system variants with different characteristic properties were evaluated for ESD scenarios, ex-vivo in two locations in the stomach and colorectum.Results In total 28 ESDs were performed (7 antrum, 7 corpus in inversion, 7 cecum, 7 rectum) in a porcine ex-vivo setup. ESD was feasible in 21 cases. Investigated manipulator variants are differently well suited for performing ESD within the varying interventions scenarios. Dual-arm manipulators allowed autonomous ESD, while single-arm flexible manipulators could be used more universally due to their compact design, especially for lesions difficult to access. Pediatric scopes were too frail to guide the overtube-manipulators in extremely angled positions. Working in the rectum was impaired using long-sized manipulator arms. Conclusions The presented endoscopic platform based on 3D-printable and customizable manipulator structures might be a promising approach for future improvement of ESD procedure. With regard to localization, especially flexible manipulators attached to standard endoscopes appear to be most promising for further application of specific and individualised manipulator systems.